Intercultural communication in three Eastern Cape HIV/AIDS clinics - Mandla, Veliswa Maureen (Rhodes University, Faculty of Humanities, School of Languages, 2009)
There are many inequities that exist in health-care that stem from culture related communication misunderstandings. In most cases where doctors and patients from different cultural and linguistic background interact, doctors use medical language which is different from everyday language used by patients. Patients enter this communication context with anxiety because they depend on the physicians to give them accurate information concerning their health, but they do not always understand all the terms used by physicians to inform them about their conditions. In some cases interpreters are used but their expertise is often inadequate and the interpreting of the patient's statements to the health staff is also prone to distortion by interpreter / doctor because of the lack of proper understanding of the messages / languages. This may result in a deterioration of the patient's health condition and unavoidable complications.
Keywords: Intercultural communication -- South Africa -- Eastern Cape; HIV-positive persons -- South Africa -- Eastern Cape; HIV-positive persons -- Medical care -- South Africa -- Eastern Cape; AIDS (Disease) -- Patients -- South Africa -- Eastern Cape; Xhosa language -- Study and teaching -- English speakers; Physician and patient -- South Africa -- Eastern Cape; Communication in medicine -- South Africa -- Eastern Cape